2019
DOI: 10.2147/idr.s213525
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genetic characterization of a novel sequence type of multidrug-resistant <em>Citrobacter freundii</em> strain recovered from wastewater treatment plant</p>

Abstract: A multidrug-resistant Citrobacter freundii strain R17 was isolated from a wastewater treatment plant in China. Whole-genome sequencing of strain R17 revealed a new sequence type (ST412) chromosome (length 5,124,258 bp) and an Inc FII (Yp) group plasmid pCFR17_1 (length 206,820 bp). A total of 13 antibiotic-resistance genes (ARGs) that confer resistance to eight different antibiotic groups were encoded by strain R17 and 12 of them were carried by plasmid pCFR17_1. These data and analysis suggest that the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…This result further supported the previous hypothesis that bla CMY genes were ubiquitous in CFC isolates. 19 S1-PFGE and Southern blot demonstrated that DY2019 encoded two plasmids (Figure 1), and bla NDM-1 was located on a ~348 kb novel IncHI2 plasmid (Figure 2). Interestingly, the principal NDM variant found in CFC was bla NDM−1 , which is usually located on the self-transferable IncX3 plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result further supported the previous hypothesis that bla CMY genes were ubiquitous in CFC isolates. 19 S1-PFGE and Southern blot demonstrated that DY2019 encoded two plasmids (Figure 1), and bla NDM-1 was located on a ~348 kb novel IncHI2 plasmid (Figure 2). Interestingly, the principal NDM variant found in CFC was bla NDM−1 , which is usually located on the self-transferable IncX3 plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…18 Bacterial identification was performed by both VITEK2 compact system (BioMerieux, France) and Microflex MALDI-TOF mass spectrometer (Bruker Daltonics, Bremen, Germany) as described previously. 6,19 Using ANI analysis, species were determined if the genome in question had >95% ANI value with the type genome using pyani with default settings (https://github.com/widdowquinn/pyani).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Citrobacter spp. has been speculated as a potential source for carrying and spreading of antibiotic resistant genes ( Jiang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…are common Gram-negative bacilli and widely found in water, food, soil, and intestines of animals and humans [ 21 ]. AMR encoding genes are frequently reported in Citrobacter freundii , and it became a reservoir of antibiotic resistance genes in recent years [ 22 , 23 ]. In addition, MDR C. freundii has been reported in numerous hosts including but are not limited to humans [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%